Two-Year Follow-Up after Contact Force Sensing Radiofrequency Catheter and Second-Generation Cryoballoon Ablation for Paroxysmal Atrial Fibrillation: A Comparative Single Centre Study. (22nd May 2016) - Kardos, Attila; Kis, Zsuzsanna; Som, Zoltan; Nagy, Zsofia; Foldesi, Csaba
Abstract : Background . There are little comparative data on catheter ablation of paroxysmal atrial fibrillation (AF) using the contact force radiofrequency (CF-RF) catheter versus the second-generation cryoballoon (CB2). Methods and results . This is a single center, retrospective, nonrandomized study of 98 patients with symptomatic, drug-refractory paroxysmal AF who underwent their first PVI ablation using either the CB2 (n = 40 ) or CF-RF (n = 58 ). The mean age was 60 years with 63% men, a mean LA size of 42 mm. The procedure duration (74 ± 17 versus 120 ± 49 minutes p < 0.05 ) was shorter for CB2 group; the fluoroscopy time (14 ± 17 versus 16 ± 5 minutes, p = 0.45 ) was similar. Complete PVI was achieved in 96% of patients with RF-CF and 98% with CB2. Phrenic nerve palsies (2 transient and 1 persistent) occurred exclusively in the CB2 group and 1 severe, nonlethal complication (pericardial tamponade) occurred in the CF-RF group. At 24-month follow-up, the success rate, defined as freedom from AF/atrial tachycardia (AT) after a single procedure without antiarrhythmic drug, was comparable in CF-RF group and CB2 group (65.5% versus 67%, resp., log rank p = 0.54 ). Conclusion . Both the CB2 and the RF-CF ablation appeared safe; the success rate at 2 years was comparable between both technologies.